2019
DOI: 10.3390/md17020086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Networking-Based Analysis of Cytotoxic Saponins from Sea Cucumber Holothuria atra

Abstract: The saponin composition of a specimen of black sea cucumber, Holothuria atra collected in the Persian Gulf was studied by a combined approach including LC-MS/MS, Molecular Networking, pure compound isolation, and NMR spectroscopy. The saponin composition of Holothuria atra turned out to be more complex than previously reported. The most abundant saponins in the extract (1–4) were isolated and characterized by 1D- and 2D-NMR experiments. Compound 1 was identified as a new triterpene glycoside saponin, holothuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…Whereas, sulphated saponins (e.g., molecular weights of m/z 1206.510 and m/z 868.389), putatively annotated as echinoside A and echinoside B respectively, were observed only in the two genera of Actinopyga and Holothuria. This is in accordance with the results from Kitagawa and colleagues (1981;1989), and Grauso and colleagues (2019), who reported echinoside A and B from Holothuria (i.e., H. atra; [79]), and Actinopyga species [80]. Actinopyga and Holothuria extracts also contained mixtures of biosides including bivittoside A like compounds (C 41 Our data indicated that the AF activity may correlate with the amount and/or type of sugar units in their glycone part (in genus Bohadschia).…”
Section: Discussionsupporting
confidence: 93%
“…Whereas, sulphated saponins (e.g., molecular weights of m/z 1206.510 and m/z 868.389), putatively annotated as echinoside A and echinoside B respectively, were observed only in the two genera of Actinopyga and Holothuria. This is in accordance with the results from Kitagawa and colleagues (1981;1989), and Grauso and colleagues (2019), who reported echinoside A and B from Holothuria (i.e., H. atra; [79]), and Actinopyga species [80]. Actinopyga and Holothuria extracts also contained mixtures of biosides including bivittoside A like compounds (C 41 Our data indicated that the AF activity may correlate with the amount and/or type of sugar units in their glycone part (in genus Bohadschia).…”
Section: Discussionsupporting
confidence: 93%
“…They can be found in a large number of plants and crops. It has the least toxic effect on non-target organisms and the environment, and plays an important role in maintaining and developing sustainable crops [10]. According to the hypotheses presented in the literature, saponins have a protective-inhibitory activity against the plant and cause gastrointestinal problems, disruption of peeling, and cytotoxicity in pests.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The powder (220 g) exhaustively extracted five times in 1 L EtOAc: methanol (1:1). The crude extract (35 g) was partitioned successively through Kupchan partitioning method to hexane, dichloromethane, BuOH and water (17). The BuOH extract (15 g) was fractionated by medium PLC (MPLC) on RP-18 25-40 μm) eluted with H2O: MeOH (0-100%, stepwise) to give 80 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…The biological activity of saponins is generally attributed to their strong membranolityc action following their interaction with sterols of cellular membrane (15). Saponins from holothurians seem to have an ecological role as defense compounds against predators (16), although they can also have a significant function in attracting symbionts (17).…”
Section: Introductionmentioning
confidence: 99%